PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS IT DI SDN PAMOTAN II - SITI NURIYATIN (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2018)
This community service program aims toaddress the problem of teachers. The student do not interested when learning in the classroom. One of the causes of the problem is because the teachers do not use the attractive tools of teaching. The effect of this condition is students can not understand the information optimally. This activity is done in 3 stages. In the first phase,observations are made to the program objectives to determine the method of the training in accordance with conditions and situation of the target.In the second stage of the implementation phase, trainingon how to make and use the tools of teaching based IT. At the last phase,follow-up is consultation or guidance for teachers make tools of theaching based IT. The result of this activity shown that the teacher use tools of teaching based IT was increase.